2022
DOI: 10.1186/s12891-022-05360-3
|View full text |Cite
|
Sign up to set email alerts
|

Effection of monoplanar pedicle screw on facet joint degeneration in thoracolumbar vertebral fractures

Abstract: Background This study aimed to compare the clinical outcomes and effect on instrument-related facet joints between fixed-axis pedicle screw (FAPS) and monoplanar pedicle screw (MPPS). Methods 816 pedicle screws of 204 patients with thoracolumbar vertebral fractures (TLVF) who underwent internal fixation surgery were analyzed in this retrospective study. All patients were divided into two groups (FAPS and MPPS). Preoperative, immediate postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Similarly, a clinical study by Huang et al [ 37 ] indicated that MSs fixation achieved better correction effect and less correction loss than polyaxial screw fixation alone. According to Ye et al [ 38 ] MS probably a superior option to reduce the incidence of degeneration of the injured vertebral adjacent segment than fixed axial screw.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a clinical study by Huang et al [ 37 ] indicated that MSs fixation achieved better correction effect and less correction loss than polyaxial screw fixation alone. According to Ye et al [ 38 ] MS probably a superior option to reduce the incidence of degeneration of the injured vertebral adjacent segment than fixed axial screw.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with UPPS experienced less intraoperative bleeding and spent less time in the hospital. Additionally, when it comes to restoring the anterior vertebral body’s height following surgery, UPPS and FAPS have comparable results ( Ye et al, 2022 ). This demonstrates that UPPS combines the advantages of FAPS and PAPS, ensuring sufficient biomechanical stability while facilitating the operation and reducing the risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…PPSF may increase ASD has been reported in the literature ( 19 ). The reason for this may be that the posterior lumbar spine surgery damages the lower back muscles and adjacent facet joints ( 49 , 50 ), increasing ASD. Limited by the number of cases, our study did not find a statistically significant reduction in ASD with OLIF stand-alone.…”
Section: Discussionmentioning
confidence: 99%